Effects of intradermal acupuncture in relieving the non-incisional pain and promoting anal exhaust and defecation after gynecological laparoscopy (皮内针在缓解妇科腹腔镜术后非切口疼痛及促进排气排便中的效果观察) - LIU Xiaoyu (刘晓宇); XU Daoli (徐道立); LIU Ying (刘颖); LU Yin (卢英) (中西医结合护理)
Objective To investigate the clinical effect of intradermal acupuncture, a characteristic nursing technique of Traditional Chinese Medicine, on improving non-incision pain and promoting anal exhaust and defecation after gynecological laparoscopic surgery. Methods A total of 152 patients who underwent laparoscopic surgery were selected and divided into a control group(n=60) and a treatment group(n=80). The control group was given regular care of low-flow oxygen inhalation, and the treatment group was given intradermal needle therapy based on those therapies of control group. The pain intensity of the two groups of patients at 24h, 48h, 72h postoperatively, changes in clinical symptoms, time to postoperative exhaust and defecation were compared between two groups. Results The Visual Analogue Scale (VAS)of pain of the treatment group was lower than that of the control group at 24h, 48h, 72h postoperatively(P＜0. 05), and symptom score of the treatment group was higher than that of the control group(P＜0. 05). The time to first exhaust and defecation in the treatment group was significantly shorter than that of the control group (P＜0. 05). Conclusion Intradermal needle therapy after gynecological laparoscopic surgery has a good effect on alleviating postoperative non-incision pain, and can effectively promote postoperative exhaust and defecation. (目的 探讨皮内针在缓解妇科腹腔镜术后非切口疼痛及促进排气排便中的疗效。方法 140例行腹腔镜手术的妇科患者分为对照组60例及观察组80例。对照组给予低流量吸氧及常规护理, 观察组在对照组的基础上给予皮内针治疗。观察2组患者术后非切口疼痛程度、症状改善情况以及排气、排便时间。结果 观察组术后24 h、48 h、72 h的VAS疼痛评分均低于同期对照组(P＜0. 05), 临床症状评分高于同期对照组 (P＜0. 05)。观察组术后首次排气和排便时间早于对照组, 差异有统计学意义(P＜0. 05)。结论 妇科腹腔镜术后采用皮内针进行干预对缓解术后非切口疼痛有良好效果, 且可有效促进术后排气排便。)